The Urgency of Umkm Export Policy Relaxation as a Trade Expansion Step Amid Economic Globalization - Nuzul Quraniati Rohmah (Leges Privatae, 2024)
Micro, Small and Medium Enterprises are productive economic businesses managed by business entities or individuals. The number of MSMEs in Indonesia continues to increase every year, until in 2017 based on data from the Ministry of Cooperatives and MSMEs, the number of MSMEs in Indonesia reached 62,922,617 units. The level of interest in MSME products is very high abroad, but the high level of interest is not supported by adequate regulations. Despite the high level of interest, many MSME business actors complain about the complexity of the requirements and the high cost of the licensing process to carry out export activities. Micro, Small and Medium Enterprises cannot be equated with large companies, one of which is that in terms of funding, MSMEs are still very weak, making it difficult to accommodate the requirements and licensing fees for exporting, several MSME players canceled export activities due to problems with these requirements and licensing. It is necessary to relax policies for MSMEs so that they can carry out export activities which in turn can increase the country's foreign exchange and also as a step of trade expansion to be able to compete with other countries. This journal is then made to determine the level of urgency of the relaxation of MSME export policies as an effort to expand trade in the midst of economic globalization. The method of writing is carried out with normative juridical where the author reviews this issue based on legislation and related regulations as well as literature related to export activities by MSMEs